A biomechanical comparison study of a modern fibular nail and distal fibular locking plate in AO/OTA 44C2 ankle fractures. Issue 1 (December 2016) - Switaj, Paul; Fuchs, Daniel; Alshouli, Mohammed; Patwardhan, Avinash; Voronov, Leonard; Muriuki, Muturi; Havey, Robert; Kadakia, Anish
Abstract Background A lateral approach with open reduction and internal fixation with a plate is a very effective technique for the majority of distal fibular fractures. However, this open approach for ankle fixation may be complicated by wound dehiscence and infection, especially in high-risk patients. An alternative to plating is an intramedullary implant, which allows maintenance of length, alignment, and rotation and which allows for decreased soft tissue dissection. While there has been clinical data suggesting favorable short-term outcomes with these implants, there is no current biomechanical literature investigating this technology in this particular fracture pattern. This study sought to biomechanically compare an emerging technology with an established method of fixation for distal fibular fractures that traditionally require an extensive exposure. Methods Ten matched cadaveric pairs from the proximal tibia to the foot were prepared to simulate an Arbeitsgemeinschaft für Osteosynthesefragen/Orthopaedic Trauma Association (AO/OTA) 44C2 ankle fracture and randomized to fixation with a distal fibular locking plate or intramedullary fibular rod. A constant 700-N axial load was applied, and all specimens underwent testing for external rotation stiffness, external rotation cyclic loading, and torque to failure. The syndesmotic diastasis, stiffness, torque to failure, angle at failure, and mode of failure were obtained from each specimen. Results There was no significant difference in syndesmotic diastasis during cyclic loading or at maximal external rotation between the rod and plate groups. Post-cycle external rotation stiffness across the syndesmosis was significantly higher for the locking plate than the fibular rod. There was no significant difference between the rod and plate in torque at failure or external rotation angle. The majority of specimens had failure at the syndesmotic screw. Conclusions In the present cadaveric study of an AO/OTA 44C2 ankle fracture, a modern fibular rod demonstrated less external rotation stiffness while maintaining the syndesmotic diastasis to within acceptable tolerances and having similar failure characteristics.